Proceedings of the Pacific Rim Statistical Conference for Production Engineering Big Data, Production Engineering and Statistics (ICSA Book Series in Statistics,, 2018)
This book presents the proceedings of the 2nd Pacific Rim Statistical Conference for Production Engineering: Production Engineering, Big Data and Statistics, which took place at Seoul National University in Seoul, Korea in December, 2016. The papers included discuss a wide range of statistical challenges, methods and applications for big data in production engineering, and introduce recent advances in relevant statistical methods.